Effects of topical insulin on second-intention wound healing in the red-eared slider turtle (Trachemys scripta elegans) – a controlled study - Negrini, Joao; Mozos, Elena; Escamilla-Sánchez, Alejandro; Pérez, José; Lucena, Rosario; Guerra, Rafael; Ginel, Pedro (Springer Nature, 2017)
Compared with mammals, wound healing in reptiles is characterized by reduced wound contraction and longer healing times. The aim of this study is to describe the clinical and histopathological effects of topical insulin on second-intention healing of experimentally induced wounds in skin without dermal bony plates of Trachemys scripta elegans exposed to daily variations in ambient temperature and in an aquatic environment. Forty-four healthy adult females were assigned to two groups: Group 1 (n = 24) was used to assess clinical features such as wound contraction; Group 2 (n = 20) was used for histological evaluation and morphometric analysis. Topical porcine insulin (5 IU/ml diluted in glycerol) was applied daily 1 week. For each control time (2, 7, 14, 21 and 28 days post-wounding), re-epithelisation and wound remodelling were evaluated histologically and the number of main inflammatory cells (heterophils, macrophages, lymphocytes and fibroblasts) was scored. Results Mean wound contraction was higher in the insulin-treated group at each time point and differences were significant at day 28 (P < 0.0001). Histologically, these clinical findings were associated with better re-epithelisation, inflammatory response, collagen synthesis and remodelling of the wounds. Morphometrically, insulin-treated wounds had significantly higher mean counts of heterophils (day 7), macrophages (days 2, 7 and 14) and fibroblasts (days 14 and 21), whereas lymphocyte counts were significantly lower at day 21. These results demonstrate that topical insulin modifies the inflammatory response of turtle skin up-regulating inflammatory cells at early stages and promoting wound healing. Conclusions Topical insulin is a potentially useful therapy in skin wounds of Trachemys scripta and should be evaluated in non-experimental wounds of turtles and other reptiles.
Keywords: Cicatrización; Histology; Skin; Immunopathology; Topical insulin; Wound healing